The application of SpyScope® technology in evaluation of pre and post liver transplant biliary problems - Muzaffer GÜRAKAR; Harlan WRIGHT; Cemalettin CAMCI; Nicolas JABOOUR (Turkish Journal of Gastroenterology, 2019)
-